Timing for Introduction of Total Laparoscopic Living Donor Right Hepatectomy; Initial Experience Based on the Data of Laparoscopic Major Hepatectomy. Issue 6 (June 2021) - Lee, Boram; Choi, YoungRok; Lee, Woohyung; Park, Youngmi; Kim, Kil Hwan; Hyun, In Gun; Han, Sun Jong; Cho, Jai Young; Yoon, Yoo-Seok; Han, Ho-Seong
Abstract : Background: This study evaluated the timing of safe introduction of total laparoscopic donor right hepatectomy (TLDRH) based on outcomes of laparoscopic major hepatectomy (LMH). Methods: The data of 1013 consecutive patients who underwent laparoscopic liver resection from 2003 to 2017 were reviewed; the cumulative sum method was used to evaluate the learning curve of LMH. Patients were divided into 3 groups according to the timing of introduction of TLDRH (since 2010) and learning curve of LMH. Surgical outcomes of LMH and TLDRH were evaluated. Results: Cumulative sum analysis demonstrated a learning curve of approximately 73 cases of LMH. In phase I (before the introduction of TLDRH, 2003–2009), 38 cases of LMH were performed. Phase II (after the introduction of TLDRH until learning curve of LMH, 2010–2014), 35 and 15 cases of LMH and TLDRH were performed, respectively. Phase III (after learning curve of LMH until 2017, 2014–2017), 59 and 20 cases of LMH and TLDRH were performed, respectively. In cases of LMH, there was significant improvement in the operation time 398.9 ± 140.9 versus 403.7 ± 165.2 versus 265.5 ± 91.7; P  < 0.001), estimated blood loss (1122.9 ± 1460.2 versus 1209.3 ± 1409.1 versus 359.8 ± 268.8; P  < 0.001), and open conversion rate (26.3% versus 22.9% versus 13.6%; P  = 0.026) between phases I versus II versus III. In cases of TLDRH, the operation time (567.8 ± 117.9 versus 344.2 ± 71.8; P  < 0.001), estimated blood loss (800.7 ± 514.8 versus 439.4 ± 347.0; P  = 0.004), and hospital stay (12.5 ± 4.36 versus 9.15 ± 4.84; P  = 0.025) significantly improved in phase III. Conclusions: Overcoming the learning curve of LMH before starting TLDRH is advisable to ensure donor's surgical outcomes. Abstract : Supplemental Digital Content is available in the text.